2006
DOI: 10.1051/0004-6361:20066609
|View full text |Cite
|
Sign up to set email alerts
|

AMBER/VLTI interferometric observations of the recurrent Nova RS Ophiuchii 5.5 days after outburst

Abstract: Aims. We report on spectrally dispersed interferometric AMBER/VLTI observations of the recurrent nova RS Oph five days after the discovery of its outburst on 2006 Feb. 12. Methods. Using three baselines ranging from 44 to 86 m, and a spectral resolution of λ/δλ = 1500, we measured the extension of the milliarcsecond-scale emission in the K band continuum and in the Brγ and He I 2.06 µm lines, allowing us to get an insight into the kinematics of the line forming regions. The continuum visibilities were interpre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 33 publications
12
41
0
Order By: Relevance
“…Some recent examples suggest that bipolarity in the ejecta of classical/recurrent novae may be relatively frequent: RS Oph (Ribeiro et al 2009;Bode et al 2007;Chesneau et al 2007), V445 Pup (Woudt et al 2009), V1280 Sco (Chesneau et al 2008;Chesneau et al, in prep. ) or HR Del (Harman & O'Brien 2003).…”
Section: A Face-on Bipolar Eventmentioning
confidence: 99%
“…Some recent examples suggest that bipolarity in the ejecta of classical/recurrent novae may be relatively frequent: RS Oph (Ribeiro et al 2009;Bode et al 2007;Chesneau et al 2007), V445 Pup (Woudt et al 2009), V1280 Sco (Chesneau et al 2008;Chesneau et al, in prep. ) or HR Del (Harman & O'Brien 2003).…”
Section: A Face-on Bipolar Eventmentioning
confidence: 99%
“…Numerous works studied the new outburst in multiple spectral regions, e.g., in X-rays Ness et al 2007;Vaytet et al 2007), in optical ), in infrared (Das et al 2006;Chesneau et al 2007;Evans et al 2007a,b;Lane et al 2007), and in radio wavelength . Some theoretical work on the explosion was carried out (e.g., Hachisu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These results were also contrary to Monnier et al (2006). Furthermore, Chesneau et al (2007) found two velocity fields in the Brγ line; a slowly expanding ring-like structure (v rad ≤ 1800 km s −1 ), and a fast structure extended in the E-W direction (v rad ∼ 2500-3000 km s −1 ). A two velocity component was also required to replicate the Hubble Space Telescope narrow band imaging observations of the resolved remnant, at day 155 after eruption, and the ground-based optical spectroscopy (Ribeiro et al 2009).…”
Section: Infrared Interferometric Observations Of Novae In Eruptionmentioning
confidence: 63%
“…The AMBER instrument on the Very Large Telescope Interferometer (VLTI) was also used, on day 5.5 after eruption, to measure the K-band continuum and the Brγ and HeI 2.06 µm lines (Chesneau et al 2007). The K-band emission is dominated by free-free emission and had a smaller size than the Brγ and HeI lines (3x2 mas, 5x3 mas, and 6x4 mas, respectively).…”
Section: Infrared Interferometric Observations Of Novae In Eruptionmentioning
confidence: 99%